Cardiac valve annulus manual segmentation using computer assisted visual feedback in three-dimensional image data. - Casero, R; Burton, R; Quinn, T; Bollensdorff, C; Hales, P; Schneider, J; Kohl, P; Grau, V (2010)
Annulus manual segmentation is an important tool for the study of valve anatomy and physiology, for the four main valves of the heart (mitral, tricuspid, aortic and pulmonary). In this paper we review two traditional manual segmentation approaches: slice-by-slice and interpolating a sparse set of landmarks with a spline curve. We propose a new Spline Tool for the open source software platform Seg3D, that is fast and improves spatial coherence by providing visual feedback of the segmentation in real time. The Spline Tool was tested successfully on 14 rat hearts, on all four valves.